Phenotypic Plasticity Provides a Bioinspiration Framework for Minimal Field Swarm Robotics - Hunt, Edmund R. (Frontiers in Robotics and AI, 2020)
The real world is highly variable and unpredictable, and so fine-tuned robot controllers that successfully result in group-level ‘emergence’ of swarm capabilities indoors may quickly become inadequate outside. One response to unpredictability could be greater robot complexity and cost; but this seems counter to the ‘swarm philosophy’ of deploying (very) large numbers of simple agents. Instead, here I argue that bio-inspiration in swarm robotics has considerable untapped potential in relation to the phenomenon of phenotypic plasticity: when a genotype can produce a range of distinctive changes in organismal behaviour, physiology and morphology in response to different environments. This commonly arises following a natural history of variable conditions; implying the need for more diverse and hazardous simulated environments in offline, pre-deployment optimization of swarms. This will generate – indicate the need for – plasticity. Biological plasticity is sometimes irreversible; yet this characteristic remains relevant in the context of minimal swarms, where robots may become mass-producible. Plasticity can be introduced through the greater use of adaptive threshold-based behaviours; more fundamentally, it can link to emerging technologies such as smart materials, which can adapt form and function to environmental conditions. Moreover, in social animals, individual heterogeneity is increasingly recognised as functional for the group. Phenotypic plasticity can provide meaningful diversity ‘for free’ based on early, local sensory experience, contributing toward better collective decision-making and resistance against adversarial agents, for example. Nature has already solved the challenge of resilient self-organisation in the physical realm through phenotypic plasticity: swarm engineers can follow this lead.